2012
DOI: 10.6113/jpe.2012.12.2.285
|View full text |Cite
|
Sign up to set email alerts
|

DSP-Based Simplified Space-Vector PWM for a Three-Level VSI with Experimental Validation

Abstract: Multilevel inverters have gained attention in high-power applications due to their numerous advantages in comparison with conventional two-level inverters. In this paper a simplified Space-Vector Modulation (SVM) algorithm for a three-level Neutral-Point Clamped (NPC) inverter is implemented on a Freescale® DSP56F8037. The algorithm is based on a simplification of the space-vector diagram for a three-level inverter so that it can be used with a two-level inverter. Once the simplification has been achieved, cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…In paper [13] [14], SVPWM is proposed for three-phase three-level inverter by simplifying the three-level SVPWM into a two-level SVPWM diagram. In this, three-level SVPWM diagram is modified into two-level SVPWM diagram by constructing many small hexagon from three-level SVPWM diagram and dwelling times of three-level voltage vectors are calculated in same manner as two-level.…”
Section: Introductionmentioning
confidence: 99%
“…In paper [13] [14], SVPWM is proposed for three-phase three-level inverter by simplifying the three-level SVPWM into a two-level SVPWM diagram. In this, three-level SVPWM diagram is modified into two-level SVPWM diagram by constructing many small hexagon from three-level SVPWM diagram and dwelling times of three-level voltage vectors are calculated in same manner as two-level.…”
Section: Introductionmentioning
confidence: 99%
“…The suggested hybrid switches are not practically recommended as the inverter phase module switches will not have the same characteristics which will complicate the overall inverter design and limits it power rating as declared by the authors. A recent driver circuit is presented in Ramirez et al (2012) which require two IR2110 to drive each inverter leg as shown in Figure 5. The driver circuit requires four separate power supplies each for one IGBT.…”
Section: Introductionmentioning
confidence: 99%
“…Source: Ramirez et al (2012) In this paper, the design proposal in Ramirez et al (2012) is modified to include a shoot-through prevention circuit. The external dead time circuit is designed based on Schmitt trigger integrated circuit and a simple RC filter to achieve precise adjustment of the dead time in a fraction of a microsecond resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Space vector pulse width modulation could be used the composite the needed voltage, this has been illustrated in reference [16,28,29]. Yet, this need complicated mathematic computation for Clark and Park transformations, due to this, faster and higher micro-controller is needed.…”
Section: Decoupled Sliding Mode Controller Design For the Npc Vsi Basmentioning
confidence: 99%
“…A great deal of work related to the multi-level converter topology, control schemes, and their applications has been done in the last ten years [15][16][17]. Mondal et al [18] extended the space voltage pulse width modulation (SVPWM) of the three-level inverter into the over-modulation region.…”
Section: Introductionmentioning
confidence: 99%